Immunomics in Pediatric Rheumatic Diseases - Tay, Shi Huan; Yaung, Katherine Nay; Leong, Jing Yao; Yeo, Joo Guan; Arkachaisri, Thaschawee; Albani, Salvatore (Frontiers in Medicine, 2019)
The inherent complexity in the immune landscape of pediatric rheumatic disease necessitates a holistic system approach. Uncertainty in the mechanistic workings and etiological driving forces presents difficulty in personalized treatments. The development and progression of immunomics is well suited to deal with this complexity. Immunomics encompasses a spectrum of biological processes, that entail genomics, transcriptomics, epigenomics, proteomics and cytomics. In this review, we will discuss how various high dimensional technologies in immunomics have helped to grow a wealth of data that provide salient clues and biological insights into the pathogenesis of autoimmunity. Interfaced with critical unresolved clinical questions and unmet medical needs, these platforms have helped identify candidate immune targets, refine patient stratification and understand treatment response or resistance. Yet the unprecedented growth in data has presented both opportunities and challenges. Researchers are now facing huge heterogeneous data sets from different origins that need to be integrated and exploited for further data mining. We believe that the utilization and integration of these platforms will help unravel the complexities and expedite both discovery and validation of clinical targets.